The diagnostic accuracy of routine clinical findings for detection of esophageal varices in rural sub-Saharan Africa where schistosomiasis is endemic - Opio, Christopher K.; Rejani, Lalitha; Kazibwe, Francis; Ocama, Ponsiano (African health sciences, 2019)
Variceal upper gastrointestinal bleeding (UGIB) is common in sub-Saharan Africa (SSA). However, poor access to endoscopy services precludes the diagnosis of varices. Objectives: We determined the diagnostic accuracy of routine clinical findings for detection of esophageal varices among patients with UGIB in rural SSA where schistosomiasis is endemic. Methods: We studied patients with a history of UGIB. The index tests included routine clinical findings and the reference test was diagnostic endoscopy. Multivariable regression with post-estimation provided measures of association and diagnostic accuracy. Results: We studied 107 participants with UGIB and 21% had active bleeding. One hundred and three (96%) had liver disease and 86(80%) varices. Factors associated with varices (p-value <0.05) were ≥ 4 lifetime episodes of UGIB, prior blood transfusion, splenomegaly, liver fibrosis, thrombocytopenia, platelet count spleen diameter ratio <909, and a dilated portal vein. Two models showed an overall diagnostic accuracy of > 90% in detection of varices with a number needed to misdiagnose of 13(number of patients who needed to be tested in order for one to be misdiagnosed by the test). Conclusion: Where access to endoscopy is limited, routine clinical findings could improve the diagnosis of patients with UGIB in Africa.
Keywords: Diagnostic accuracy; Clinical findings; Esophageal varices; Rural sub-Saharan Africa